2015
DOI: 10.4314/ijbcs.v8i5.39
|View full text |Cite
|
Sign up to set email alerts
|

The reinforcing potentials of <i>Velvet tamarind</i> seed shell as filler in natural rubber compounds

Abstract: This work focused on the development of a reinforcing filler from renewable natural plant resources as part of the ongoing search for environmental friendly fillers that will substitute synthetic reinforcing fillers such as carbon black and silica in rubber manufacturing. The cure characteristics, physico-mechanical and equilibrium swelling properties of natural rubber, Standard Nigerian Rubber (SNR 10) vulcanizates separately filled with commercial grade carbon black (CB), N330 and pulverized natural plant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 10 publications
7
16
0
3
Order By: Relevance
“…Thus, the elongation at break decreased, and the modulus increased. The low elongation at break of the rubber vulcanizates obtained in this study implies that the rubber products would be rigid and are expected to have low hysteresis and heat build-up [17]. The observed decrease in elongation at break of PLF filled natural rubber vulcanizates with filler content is consistent with previously reported works on the variation of elongation at break of natural fibre reinforced rubber with filler content [16] [17] [21].…”
Section: Elongation At Breaksupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the elongation at break decreased, and the modulus increased. The low elongation at break of the rubber vulcanizates obtained in this study implies that the rubber products would be rigid and are expected to have low hysteresis and heat build-up [17]. The observed decrease in elongation at break of PLF filled natural rubber vulcanizates with filler content is consistent with previously reported works on the variation of elongation at break of natural fibre reinforced rubber with filler content [16] [17] [21].…”
Section: Elongation At Breaksupporting
confidence: 90%
“…with filler content maybe attributed to filler related parameters such as particle size, surface area, filler surface reactivity and also, to the increase in mixing time resulting in the introduction of the filler into natural rubber [31] [32]. Okoh et al [17] who worked on Velvettamarid seed shell and CB filled natural rubber vulcanizates reported that the scorch times of the vulcanizates decreased with increasing filler content.…”
Section: Scorch Timementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for cotton linter based composites (NR-CLNC) the tensile strength increased from 1.85 to 3.92 MPa when CLNC content was increase from 0 -30 pphr while for carbon black(NR-CB) composites, the tensile strength increased from 1.85 to 4.5MPa for CB content of 0 -30 weight %.Generally, from these data presented the tensile strength increased with increasing weight of cellulosic nanoparticles and carbon black in the rubber matrix, though carbon black gave higher values. This behaviour is manifestation of reinforcement tendencies [15] & [16] which imply that there was a strengthening effect of these particulate materials due to the role they play by imposing restriction on rubber chains molecular rupture and slippage of these chains past each other. Also the nature of predominated interface (rubberrubber, rubber-particles or particle-particle) formed and the interfacial interaction between the rubber phase and the nanoparticulate materials plays a vital role in the reinforcement of rubber matrix [4,14,17], that is the higher the ability of the rubber to spread round the particle surface during processing (good wettability) the higher the stress require to break the physical bonding between the rubber and the particle hence the higher the tensile strength.…”
Section: Tensile Strengthmentioning
confidence: 99%